2020
DOI: 10.1088/1361-651x/ab8358
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic simulations of dynamics of an edge dislocation and its interaction with a void in copper: a comparative study

Abstract: Atomistic simulation methods are appropriate tools for investigating the dynamics of dislocations and their interactions with obstacles in metallic materials. In particular, molecular dynamics (MD) simulations have been widely employed on these two topics in the past several decades. However, even for the same type of simulation, the results can vary. While some of the quantitative differences may be due to the choices of interatomic potential and simulation cell size, they could similarly be attributed to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…This potential is very suitable to reproduce the energy of various lattice defects in copper and can be used to predict the lattice distortion and local stress field. In this work, the accuracy of the local distortions and stress field effects caused by vacancies is critical [29,30]. In addition, the stacking fault energy (SFE) of copper calculated by this potential function (44.39 mJ m −2 ) is in good agreement with the experimental values (45 mJ m −2 ), which is important for correctly predicting the edge dislocation behaviors and mobility under high stresses [7,28].…”
Section: Methods and Simulationmentioning
confidence: 66%
“…This potential is very suitable to reproduce the energy of various lattice defects in copper and can be used to predict the lattice distortion and local stress field. In this work, the accuracy of the local distortions and stress field effects caused by vacancies is critical [29,30]. In addition, the stacking fault energy (SFE) of copper calculated by this potential function (44.39 mJ m −2 ) is in good agreement with the experimental values (45 mJ m −2 ), which is important for correctly predicting the edge dislocation behaviors and mobility under high stresses [7,28].…”
Section: Methods and Simulationmentioning
confidence: 66%
“…In these layers, the x , y , and z axes denote coordinates for layer M , while , , and pertain to layer . We have applied PBCs along the x (or ) and y (or ) axes, while traction-free boundary conditions are implemented along the z (or ) axis [ 14 , 47 , 48 , 49 ]. The crystallographic orientations are shown in Table 1 .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In experiments, tensile or shear deformation is performed at constant strain rate [80]. Moreover, our own MD simulations for the screw dislocation in bcc Nb and published work for an edge dislocation in fcc Cu [81] have shown that the constant-stress loading mode leads initially to shear-stress oscillations using PADs. For these reasons, we used PADs (containing 96 000 atoms) and the constantstrain loading mode under NVE conditions.…”
Section: Dynamic Screw-dislocation Propertiesmentioning
confidence: 97%